SOCIO-CULTURAL FACTORS AND THEIR IMPACT ON THE PERFORMANCE OF MULTINATIONAL COMPANIES - Masovic, Azemina (Ecoforum Journal, 2018)
Abstract The paper deals with the concepts of socio-cultural factors and performance of multinational companies. Multinational companies operate in different host countries around the world and have to deal with wide variety of economic, political, legal, socio-cultural and technological factors. One of the significant components of the business environment is a socio-cultural environment. A socio-cultural environment is a combination of social and cultural factors. Due to the strong interaction that exists between them, it is very difficult to assess their separate influence on the business operation of multinational companies. The socio-cultural factors are one of the main environmental factors that significantly affect the economic activity of multinational companies and their performance as well. Moreover, socio-cultural factors are beyond the control of foreign subsidiaries’ managers. The purpose of this paper is to describe the influence of certain socio-cultural factors on the performance of foreign subsidiaries. On the basis of the obtained results, the contribution of the paper is reflected in the determination of key socio-cultural factors that multinational companies should take into consideration in order to evaluate the actual performance of foreign subsidiaries and their managers.